2012
DOI: 10.1039/c2sm07175d
|View full text |Cite
|
Sign up to set email alerts
|

Organogel–quantum dots hybrid materials displaying fluorescence sensitivity and structural stability towards nitric oxide

Abstract: Several kinetic models for the macrocyclization of a C 2 pseudopeptide with a dihalide through a S N 2 reaction have been developed. These models not only focus on the kinetic analysis of the main macrocyclization reaction, but also consider the competitive oligomerization/polymerization processes yielding undesired oligomeric/polymeric byproducts. The effect of anions has also been included in the kinetic models, as they can act as catalytic templates in the transition state reducing and stabilizing the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 114 publications
(58 reference statements)
1
32
0
Order By: Relevance
“…Broadening of the excitation spectra suggested that the curcumin fluorophore might be influenced by the presence of molecule 1 fibril. It was reported that the excitation and emission spectra of a chromophore probe in an organogel would hardly change, if it had identical mobility of such probe in a solution [17,18]. The excitation spectra of curcumin organogel strongly suggested that the curcumin molecules were not likely to be dissolved freely in the liquid fraction of the DPH organogel.…”
Section: Enhanced Photoluminescence By Dph Organogelmentioning
confidence: 97%
See 1 more Smart Citation
“…Broadening of the excitation spectra suggested that the curcumin fluorophore might be influenced by the presence of molecule 1 fibril. It was reported that the excitation and emission spectra of a chromophore probe in an organogel would hardly change, if it had identical mobility of such probe in a solution [17,18]. The excitation spectra of curcumin organogel strongly suggested that the curcumin molecules were not likely to be dissolved freely in the liquid fraction of the DPH organogel.…”
Section: Enhanced Photoluminescence By Dph Organogelmentioning
confidence: 97%
“…The decay of PL intensity was proportional to the concentration of pyrrole and time. From the slope of the initial data sets, the apparent quenching rate r (= normalized intensity/time) was calculated for each concentration (see SI, Table S1) [17]. The quenching rates also increased with the pyrrole concentration, which supported the diffusional transportation of pyrrole in the curcumin organogel.…”
Section: Page 15 Of 41mentioning
confidence: 99%
“…Wadhavane et al reported the use of pseudopeptidic macrocycle (Fig. 20) to prepare organic/inorganic hybrid organogels [67]. Cyclophane is a macrocycle and is able to self-associate to form fibrils leading to thermo reversible organogels in a number of solvents.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Moreover, the attachment of specific ligands on their surface strongly affects their luminescent properties also providing them with colloidal stability in different media. 12 Using the same LMOG results in a symbiotic effect between QDs and the LMOG, producing an enhancement of the CdSe luminescence (ca. 8 This approach is relevant not only for the design of functional materials, but also for understanding the properties that may arise from the interactions within the components of the hybrid composite.…”
Section: Introductionmentioning
confidence: 99%